Pengaruh Gaya Hidup, Citra Merek, Kelompok Referensi, Kualitas Produk, dan Harga terhadap Keputusan Pembelian - Indira*, Christera Kuswahyu; Ridwan, Anggraeni Nur; dirnaeni, Desti; Ardiansyah, Irfan (Universitas Syiah Kuala, 2024)
Currently, almost all Indonesian people, both adults and young, like to drink coffee and this is in line with the rapid emergence of coffee shops. The purpose of this study was to determine the effect of lifestyle, brand image, reference groups, and product quality on purchasing decisions for Starbucks coffee in Bekasi city. The population in this study are consumers in the Bekasi City area who have purchased Starbucks Coffee. The samples taken in this study were 144 respondents. The sampling technique used is non probability sampling with accidental sampling method. The data used is primary data where data collection is obtained by distributing online questionnaires to Starbucks Coffee consumers. The test tool used is SPSS with several analytical techniques, namely validity test, reliability test, classic assumption test, F test, multiple linear regression, T test, dominant test, and the coefficient of determination (R). The results of this study indicate that the variables of lifestyle, brand image, reference group, and product quality partially influence the decision to buy Starbucks coffee. Lifestyle, brand image, reference group, and product quality variables simultaneously influence purchasing decisions, and the most dominant variable on purchasing decisions is product quality.